Discrepancy and spatial grouping of individual potential among Kebumen Ongole Grade cattle farmers in Kebumen Regency - Sugiarto, M.; Nur, S.; Djatmiko, O. E.; Gayatri, S. (Diponegoro University, 2019)
This research aimed to analyze the discrepancy in individual potential of Kebumen Ongole Grade cattle farmers, and analyze spatial grouping based on the farmers’ individual potential. The study was conducted using survey method among cattle farmers in 6 districts which are the development centers of Kebumen Ongole Grade cattle in Kebumen Regency (District of Puring, Petanahan, Klirong, Mirit, Bulus Pesantren, and Ambal). One hundred Kebumen Ongole Grade cattle farmers were selected using multistage sampling method. The data were analyzed using descriptive statistics and Theil Entropy Index analysis to describe the level of discrepancy of farmers’ individual potential. The cattle farmers have relatively sufficient individual potential with total score 521.14. Based on Theil Entropy Index, discrepancy in individual potential was relatively high (5.29). Partially, the cattle farmers’ discrepancy was relatively high in the provision of production input (6.06), provision of work force potential (6.60), and basic potential (5.11). The production facilities need to be made available in order to accelerate farmers’ individual potential and to reduce the discrepancy in individual potential among farmers. The western part of the cattle development area of Kebumen Regency must be given priority to realize the uniformity of the potential of individual farmers.